RESEARCH OF IRON EXTRACTION FROM PRIMARY STEELMAKING SLAG - Bykov, Petr; Bogomolov, Alexey; Bitkeyeva, Alya; Nurgozhin, Renat (Journal of Applied Engineering Science, 2023)
The article examines the issue of involving primary steelmaking slag in the processing with the extraction of iron and the production of slag, which can be used in the manufacture of construction products. Currently, primary steel slag is not used for the production of construction products due to the large amount of iron, and its use is limited to road construction and in most cases, primary slag is sent to landfills. In the Pavlodar region of the Republic of Kazakhstan, during steel production at electric steelmaking enterprises, the resulting electric furnace slag and dust are stored in slag dumps. They are practically not used, despite their high content of iron oxides and metallic iron particles (up to 40% by weight in some types of slag). The work experimentally determined the chemical and mineralogical composition of primary electric furnace slag with a total iron content of more than 20%. The slag contains the following minerals: wüstite (FeO), magnetite (Fe3O4), gehlenite (Ca2Al(Al,Si)2O7), merwinite (Ca3Mg(SiO4)2). In the course of experimental studies on the recycling of primary electric furnace smelting slags by reduction induction melting of slag-lime-coke pellets, the possibility of extracting iron in the form of iron-carbon alloys and using the slags for the production of concrete was established.
Keywords: metallurgy, steel, slag, recycling, X-ray spectral analysis